2010
DOI: 10.3724/sp.j.1206.2009.00360
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 Mediated The Vasodilatation of Apelin-13 on Vascular Rings of Spontanously Hypertensive Rat <I>in vitro</I>*

Abstract: 李兰芳 2) 苏桃 2) 陈临溪 2)***( 1) 南华大学附属第一医院心内科,衡阳 421001; 2) 南华大学药物药理研究所,衡阳 421001) 摘要 研究自发性高血压大鼠(spontanouslyhypertensiverat,SHR)离体血管环对 G 蛋白偶联受体 APJ 的内源性配体 apelin-13 的血管收缩与舒张反应及其与一氧化氮(NO)和 ERK1/2 通路关系. 采用离体血管环体外灌流方法用 Power-Lab 生物信息采集 仪检测血管环的张力. 实验分组如下:新福林(Phenylephrine,PE)组,乙酰胆碱(acetylcholine, Ach)组,apelin-13 组, apelin-13 + PE 组,apelin-13 + Ach 组,PD98059(ERK1/2 抑制剂)+ PE 组,PD98059 + Ach 组,LNNA(L-nitro-arginine,硝基左 旋精氨酸,一氧化氮合酶抑制剂) +PE 组,LNNA+Ach 组,apelin-13(预孵育) + PD98059 + PE 组,apelin-13(预孵育)+PD98059+ Ach 组,apelin-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Our laboratory has been studied the effect of apelin/APJ on the cardiovascular system for several years. We demonstrated that apelin-13 reduced blood pressure (Li et al, 2007) and promoted vasodilatation of vascular rings on spontaneously hypertension rat in vitro which was mediated by extracellular signal-regulated kinases 1 and 2 (ERK1/2) (Liu et al, 2009). Besides, we also reported that apelin-13 promoted cardiomyocytes (Xie et al, 2015).…”
Section: Discussionmentioning
confidence: 88%
“…Our laboratory has been studied the effect of apelin/APJ on the cardiovascular system for several years. We demonstrated that apelin-13 reduced blood pressure (Li et al, 2007) and promoted vasodilatation of vascular rings on spontaneously hypertension rat in vitro which was mediated by extracellular signal-regulated kinases 1 and 2 (ERK1/2) (Liu et al, 2009). Besides, we also reported that apelin-13 promoted cardiomyocytes (Xie et al, 2015).…”
Section: Discussionmentioning
confidence: 88%
“…Apelins and APJ are widely expressed in animal and human heart, lung, kidney, brain, liver, breast, and skeletal muscle and abundantly found in cardiovascular, brain, lung, and breast cancers. Previous studies have shown that apelin/APJ system has effects on the function of cardiovascular system [4], has the functional and histopathological protective effects against renal ischemia/ reperfusion injury [5], and has the effect of analgesia [6]. In addition, apelin/APJ system is involved in many processes such as regulation of the release of hormone and metabolism [7], regulation of cell proliferation, migration, and apoptosis [8], and reduction of pulmonary inflammation and fibrin deposition [9].…”
Section: Introductionmentioning
confidence: 99%
“…Animal and human studies suggested that it might play a role in the pathogenesis of heart failure by modulating the harmful effects of Ang II [8,9]. The diastolic reactivity of apelin in ex vivo vascular rings of SHR (spontanously hypertensive rat) is reduced and the effect is mediated by NO pathway and the ERK1/2 pathway [10]. High levels of both APJ and apelin mRNA are found in cardiac myocytes, vascular smooth muscle, and endothelial cells of large conduit arteries, coronary vessels, and endocardium of the right atrium [11 -13].…”
Section: Introductionmentioning
confidence: 99%